Sistema de Garantia de Direitos da Criança e do Adolescente: estrutura e organização no enfrentamento da violência, Feira de Santana-BA - Oliveira, Maria Nice Dutra de (2011)
Objective: to describe the structure and organization of the Instances that integrate the Guarantee System of Rights of the Child and Adolescent, Feira de Santana/BA, in 2010. Method: cross-sectional, census, applied through forms with 101 technicians and coordinators. Results: Among the 11 Instances, more than 90% had a suitable infrastructure, satisfactory operational support (81.9%), easy access (63.6%) and inter-institutional partnerships (90%). The most frequent denunciations (48.9%) were made by the people from the local community through the emergency number: (dial 100), 73.3% of the cases were directed, mainly, to The Guardianship Council, and only 36.7% of them with counter-reference. Women represented the highest number among the interviewed professionals: (69.3%); most of them (54%) were between 24 and 39 years old. The level of schooling was 58,4% high school or had a technical course and 41.6% had graduate course; the majority of these professionals had between 1 and 10 years of experience in dealing with case notification, attendance for the families and their aggressors, and investigation of the cases. The knowledge of the professionals about normative attributions of the Instances pointed out that the absolute majority has a satisfactory performance, except the guardianship advisers. Conclusions: the Instances of the SGRCA of the city have suitable infrastructure and operational support to the attendance; however there is a need to improve the guardianship advisers‟ technical knowledge, as well to enforce the normative attributions of each Instance.